Affective Perception of Disposable Razors: A Kansei Engineering Approach - Razza, Bruno; Paschoarelli, Luis Carlos [UNESP] (Elsevier, 2015)
In recent decades, the market of consumer products has changed from the production-oriented point of view to a more market-focused, i.e. aiming to attend consumers’ expectations. Today, consumers turn their attention not only to the logical and rational aspects of the product, but increasingly symbolic and emotional factors have gained an important role in buying decision. Some methods have already been used to design emotional meaning in the products, such as the Kansei Engineering with reported results in literature. This study had as a goal to investigate affective aspects of disposable razors perceived by the users and how they relate to product features using Kansei Engineering. Thus, 40 disposable razors commonly found in the international market were evaluated in a virtual system through a variety of pictures (photographic representation) of the products. In order to identify the most relevant product features Morphological Analysis was performed. To evaluate the disposable razors, 321 male adults volunteered in this study. Semantic differential with 17 pairs of bipolar adjectives were employed to construct the semantic space in Kansei Engineering. The results showed no high correlation in the sample. Moderate correlations, however were found in 12 pairs of bipolar adjectives with 13 product features. Thus, it can be assumed that affective responses can be mildly related to product feature, considering limitation of statistic treatment.
Keywords: Disposable Razor.; Emotional Design; Factor Analysis; Kansei Engineering; Semantic Differential